Participatory approaches in water research: A review. (17th January 2022) - Roque, Anais; Wutich, Amber; Quimby, Barbara; Porter, Sarah; Zheng, Madeleine; Hossain, Mohammed Jobayer; Brewis, Alexandra
Abstract: Participatory research approaches address a range of problems in water research, including the under‐valuation of local knowledge, exclusion of marginalized people, preferential treatment of elite and expert perspectives, and extractive and exploitative research practices. Beyond this, a number of participatory approaches to water research are designed to empower participants, democratize knowledge production, improve decision‐making, and help bring about new environmental futures. In this primer, we map participatory research approaches and explain how they have been applied to advance water research. Our review focuses on the following eight approaches: participatory action research, community‐based participatory research, participatory rural appraisal, stakeholder research, participatory modeling, photovoice, citizen science, and sustainable future scenarios. We conclude by discussing a new approach, Participatory Convergence research, including how it builds from other approaches and its prospects to advance water research. This article is categorized under: Human Water > Water Governance Engineering Water > Methods Abstract : In water research, participatory approaches engage participants beyond research subjects to allow them to have an active voice and engagement in their own problems and possible solutions. Photo by Jason Goodman on Unsplash.